Late Silurian cephalopods from Langkawi, Malaysia, with peri-Gondwanan faunal affinity - Niko, Shuji; Sone, Masatoshi; Leman, Mohd Shafeea (Taylor & Francis, 2018)
Nine species of late Pridoli (latest Silurian) orthocerid cephalopods are described from the Upper Setul Limestone of Pulau Langgun, Langkawi Islands, Malaysia. These are the orthoceratids Michelinoceras (Michelinoceras) cf. michelini (Barrande, 1866), Michelinoceras? sp., Kopaninoceras setulense sp. nov., Mimogeisonoceras? langgunense sp. nov., Kionoceras? sp. and Orthocycloceras sp.; the arionoceratids Arionoceras mahsuri sp. nov. and Caliceras mempelamense sp. nov.; and the geisonoceratid Murchisoniceras? sp. This is the first detailed record with taxonomic descriptions of Silurian cephalopods from Southeast Asia. The assemblage belongs to the newly defined Kopaninoceras Fauna that is interpreted to have been widely distributed along the northern (African to Asian) margin of Gondwana and around the Prototethys Ocean during the late Silurian. The Kopaninoceras Fauna includes a local assemblage from the Kurosegawa Belt of south-west Japan, which possibly represents its northernmost occurrence. The distribution of the Kopaninoceras Fauna implies that the cephalopod faunas of Kazakhstan and adjacent areas in Central Asia have closer affinities with peri-Gondwanan faunas than with Baltica or Siberia, corroborating conclusions drawn by earlier researchers based on the benthic faunas. http://zoobank.org/urn:lsid:zoobank.org:pub:DDE20872-C142-4B78-B5F2-2E604C3C8689.